A review on prioritization techniques in regression testing - Rava, Mohammad (Science and Engineering Research Support Society, 2016)
Due to dynamic changing business and operating environment, software evolution is inevitable. As software evolves, there is a need for a retest of the system in order to ensure its validity and thus regression testing assures that this happens. Regression Testing has several research categories, one of the most popular areas is Test Case Prioritization which orders test cases based on a particular criteria to be tested in accordance to available resources, and thus ensuring that the most critical test cases are tested first. In this study we examine the different types of test case prioritization and a description of the techniques presented alongside the issue raised in each study. This will give an insight into the main problems currently plaguing test case prioritization and thus pave way for further research areas to tap into.